Let me see you!: video experiment on the social dimension of risk preferences - Werner Güth; Maria Vittoria Levati; Matteo Ploner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Previous studies have shown that decision makers are less other-regarding when their own payoff is risky than when it is sure. Empirical observations also indicate that people care more about identifiable than unidentiiable others. In this paper, we report on an experiment designed to explore whether rendering the other identiiable via a short speechless video can affect the relation between other-regarding concerns and attitudes toward social risk. For this sake, we elicit risk attitudes under two treatments differing in whether the actor can see the other or not. We find that seeing the other does not affect behavior significantly: regardless of the treatment, individuals are mainly self-oriented as to social allocation of risk, though they are other-regarding with respect to expected payoff levels.
Keywords: C90; D63; D81; 330; Risk attitudes; other-regarding concerns; identifiability; Risikopräferenz; Soziale Beziehungen; Test